Biogeographic evaluation of forest landscapes of Artikutza (Navarre), from the application of the LANBIOEVA evaluation method - Lozano Valencia, Peio José; Latasa Zaballos, Itxaro; Dorronsoro Loiarte, Beñat (Geographicalia, 2015)
This paper is based on a research work developed over 20 years that aims to consolidate a method for making biogeographical inventories and evaluations of vegetal landscapes in mid and high latitudes. To date, the method has been applied to different ecosystems within the Iberian Peninsula. However, in order to assess the robustness of the method, it has been also applied to other areas. This article exposes and analyzes the overall results obtained in the area of Artikutza, Northwest of Navarre. The methodology is based on a systematic inventory of different units along with an assessment based on natural, territorial, cultural, management and risks criteria. The results, in this case, show a clear preponderance of the riparian forests, followed by oak and beech forests. A second group would be plantation forests: wild pine forest, northern red oak and fir-false cupresal.